Mediating effect of gestational weight gain on the preventive effect of exercise during pregnancy on macrosomia: a randomized clinical trial - Xuanjin Yang; Guifang Wang; Nana Liu; Yaxin Wang; Suhan Zhang; Hang Lin; Can Zhu; Li Liu; Yin Sun; Liangkun Ma (BMC, 2024)
Abstract Objective We sought to investigate the impact of individualized exercise guidance during pregnancy on the incidence of macrosomia and the mediating effect of gestational weight gain (GWG). Design A prospective randomized clinical trial. Setting A Hospital in Xingtai District, Hebei Province. Population Older than 20 years of age, mid-pregnancy, and singleton pregnant women without contraindications to exercise during pregnancy. Methods A randomized clinical trial was conducted from December 2021 to September 2022 to compare the effects of standard prenatal care with individualized exercise guidance on the incidence of macrosomia. Main outcome measure Incidence of macrosomia. Results In all, 312 singleton women were randomized into an intervention group (N = 162) or a control group (N = 150). Participants who received individualized exercise guidance had a significantly lower incidence of macrosomia (3.73% vs. 13.61%, P = 0.002) and infants large for gestational age (9.94% vs. 19.73%, P = 0.015). However, no differences were observed in the rate of preterm birth (1.86% vs. 3.40%, P = 0.397) or the average gestational age at birth (39.14 ± 1.51 vs. 38.69 ± 1.85, P = 0.258). Mediation analysis revealed that GWG mediated the effect of exercise on reducing the incidence of macrosomia. Conclusion Individualized exercise guidance may be a preventive tool for macrosomia, and GWG mediates the effect of exercise on reducing the incidence of macrosomia. However, evidence does not show that exercise increases the rate of preterm birth or affects the average gestational age at birth. Trial registration The trial is registered at www.clinicaltrails.gov [registration number: NCT05760768; registration date: 08/03/2023 (retrospectively registered)].